Galveston Orientation and Amnesia Test: applicability and relation with the Glasgow Coma Scale Galveston Orientation and Amnesia Test: aplicabilidad y relación con la Escala de Coma de Glasgow Galveston Orientation and Amnesia Test: aplicabilidade e relação com a Escala de Coma de Glasgow - Silvia Cristina Fürbringer e Silva; Regina Marcia Cardoso de Sousa (Universidade de São Paulo, 2007)
Restrictions in the application of the Galveston Orientation and Amnesia Test and questionings about the relationship between conscience and post-traumatic amnesia motivated this study, which aims to identify, through the Glasgow Coma Scale scores, when to initiate the application of this amnesia test, as well to verify the relationship between the results of these two indicators. The longitudinal prospective study was carried at a referral center for trauma care in São Paulo - Brazil. The sample consisted of 73 victims of blunt traumatic brain injury, admitted at this institution between January 03rd and May 03rd 2001. Regarding the applicability, the test could be applied in patients with a Glasgow Coma Scale score > 12; however, the end of post traumatic amnesia was verified in patients who scored > 14 on the scale. A significant relationship (r s = 0.65) was verified between these measures, although different kinds of relationship between the end of the amnesia and changes in consciousness were observed. Restricciones en la aplicación del Galveston Orientation and Amnesia Test y los cuestionamientos sobre la relación entre conciencia y amnesia post-traumática motivaron este estudio que visa identificar, a través de la puntuación de la Escala de Coma de Glasgow, el periodo más adecuado para la aplicación de la prueba de amnesia, y observar la relación entre los resultados de esos dos indicadores. El estudio prospectivo y longitudinal fue realizado en un centro de referencia para traumas en São Paulo - Brasil. El número fue de 73 victimas de trauma craneoencefálico contuso, internadas en esta institución en el periodo de 03/01 a 03/05/2001. Con relación a la aplicabilidad, la prueba puede ser aplicada en los pacientes con la Escala de Coma de Glasgow > 12, pero el término de la amnesia post-traumática fue observado en los pacientes con puntuación > 14 en la escala. Correlación significativa (rs = 0,65) fue observada entre esas medidas, aunque diferentes formas de relación entre el término de la amnesia y alteración de conciencia fueron observadas. Restrições na aplicação do Galveston Orientation and Amnesia Test e questionamentos sobre a relação entre consciência e amnésia pós-traumática motivaram este estudo que visa identificar, pelos escores da Escala de Coma de Glasgow, quando iniciar a aplicação desse teste de amnésia, bem como verificar a relação entre os resultados desses dois indicadores. O estudo prospectivo longitudinal foi realizado em centro de referência para atendimento de trauma em São Paulo - Brasil. A amostra foi de 73 vítimas de trauma craniencefálico contuso, internadas nessa instituição, no período de 3/1 a 3/5/2001. Com relação à aplicabilidade, o teste pôde ser aplicado nas vítimas com Escala de Coma de Glasgow > 12, porém, o término da amnésia pós-traumática foi verificado nos pacientes com pontuação >14 nessa escala. Correlação significativa (r s= 0,65) foi verificada entre os indicadores, no entanto, diferentes formas de relação entre término de amnésia e alteração da consciência foram observadas.